Strategi Segmentasi Pasar dalam Pemberdayaan Penyandang Disabilitas melalui Usaha Loper Koran di Dinoyo - Indrihastuti, Poppy; Suprojo, Agung; Lestari, Wulan Puji (Universitas Tribhuwana Tunggadewi Malang, 2025)
People with disabilities in Dinoyo face economic challenges due to the decline of the print media industry. This program aims to empower them through market segmentation strategies in the newspaper delivery business. The methods applied include market segmentation strategy training, operational assistance, and the